Presoaking of Hamstring Autografts in Vancomycin Decreases the Occurrence of Infection Following Primary Anterior Cruciate Ligament Reconstruction. Issue 9 (25th September 2019) - Figueroa, David; Figueroa, Francisco; Calvo, Rafael; Lopez, Mario; Goñi, Ignacio
Background: Postoperative septic arthritis is an uncommon but potentially devastating complication after anterior cruciate ligament (ACL) reconstruction. Our group started presoaking grafts with vancomycin to decrease this risk. Purpose: To compare the rate of septic arthritis in primary hamstring autograft ACL reconstruction with and without vancomycin-presoaked grafts. Study Design: Cohort study; Level of evidence, 3. Methods: Consecutive periods were studied, inclusive of April 2013 through October 2015 (pre-vancomycin protocol) and November 2015 through May 2018 (vancomycin protocol). A total of 490 patients were included in the study: 230 in the pre-vancomycin protocol and 260 in the vancomycin protocol. All patients who underwent a primary hamstring autograft ACL reconstruction by 2 senior surgeons during the periods studied were included. The final outcome studied was occurrence of highly probable postoperative septic arthritis in both groups. Diagnosis of probable septic arthritis was made by clinical diagnosis as well as cytological analysis of joint aspiration (cell count >50, 000/μL and >90% neutrophils). Statistical analysis was performed with the Fisher exact test. Significance was set at P < .05. Results: Four cases of probable postoperative septic arthritis were noted in the pre-vancomycin protocol (1.7%; 2 cases per surgeon), while no cases of septic arthritis were noted in the vancomycin protocol during the study period ( P < .05). Diagnosis was made at a mean 21.7 days (range, 16-25 days). Staphylococcus epidermidis was isolated in 2 cases, and in the other 2 cases, no organism was isolated. Conclusion: Presoaking of hamstring autografts in vancomycin for primary ACL reconstruction prevented the occurrence of postoperative septic arthritis during the study period as compared with no soaking of the grafts.